Encyclopedia Brown finds the clues - Sobol, Donald J.; Shortall, Leonard (New York : Puffin Books, 2007)
Encyclopedia Brown solves ten mysteries, from recovering a client's prized tooth collection, to following a trail of paint to find a sneaky thief, and more.
Ages 7 up.
Keywords: Detective and mystery stories; Detective and mystery fiction